Analysis of Consumer Satisfaction with the Quality of Smoked Fish Products at the Kenjeran Smoked Fish Center, Surabaya City - Gilang Rusrita Aida; Angga Pratama Putra; Rosidah Wahyu Ningtyas; Didik Budiyanto; Maria Erlinda Sarida; Filemon Cabrin Agun (Universitas Islam Lamongan, 2024)
Kenjeran is one of the coastal villages in the city of Surabaya. It is one of the coastal tourist attractions in Surabaya, famous as a center for smoked fish. The processing and marketing of smoked fish at the Kenjeran Smoked Fish Center still cannot be said to be hygienic and the sanitation aspect is still not taken into account, so it is necessary to analyze the level of consumer satisfaction as input for improving the quality of smoked fish in Kenjeran to increase the sales turnover of smoked fish. The methods used to analyze consumer satisfaction include the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Data was taken through a questionnaire to respondents who were determined using purposive sampling. The research results show that the level of consumer satisfaction based on the CSI value is already satisfactory. Then, based on the IPA Performance Analysis Index, no attribute is the main priority for improving the performance of smoked fish products. This is because the attributes of price, freshness, hygiene, safety for consumption, and product durability have entered quadrant II and their performance must be maintained. Meanwhile, the attributes of savory taste, attractive aroma, sameness, wholeness, water content, and organic processing fall into quadrant III, which means that these attributes are considered less important by consumers and the level of performance is still not in line with what consumers expect.